Overview of the Effects and Influence of the Activity of Mount St. Helens in the 1980s - Peterson, Donald (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary The cataclysmic eruption of Mount St.Helens on May 18,1980, made an enormous impact on the science of volcanology. The eruption was in daylight in clear weather, which provided an unprecedented opportunity to investigate relations among observations, products, and effects of a large explosive eruption. The May 18 events and subsequent activity stimulated perhaps the most intensive studies ever made at an active composite volcano, leading to greatly enhanced insights into both geologic and hydrologie processes operative in explosive volcanism. The eruption also disrupted much of the social and economic fabric of the Pacific Northwest. Volcanologists were called upon to explain the activity, in lay-man's terms, to government and corporate officials, the news media, schools, and the public at large. People eventually learned to live with the volcano and its uncertainties, and volcanologists better learned their role in helping society deal with a major natural disaster. Difficulties encountered at volcanicc rises elsewhere in the world in the 1980s demonstrate that these are hard lessons. In future years, a paramount challenge for scientists will be to help society apply what has been learned at Mount St. Helens to crises both nearby and far away.